Corrected Scoliosis, Cholinesterase Deficiency, and Cesarean Section: A Case Report - Roy Somers; Yves Jacquemyn; Luc Sermeus; Marcel Vercauteren (Case Reports in Medicine)
We describe a patient with severe scoliosis for which corrective surgery was performed at the age of 12. During a previous caesarean section under general anaesthesia pseudocholinesterase deficiency was discovered. Ultrasound guided spinal anaesthesia was performed enabling a second caesarean section under loco-regional anaesthesia.